1986
DOI: 10.1073/pnas.83.11.3791
|View full text |Cite
|
Sign up to set email alerts
|

Small-angle neutron scattering studies of chlorophyll micelles: Models for bacterial antenna chlorophyll

Abstract: Micelles of hydrated chlorophyll a (P740), bacteriochlorophyll a (P865), bacteriochlorophyll c (P750), and pheophytin a prepared in organic media have been studied by small-angle neutron scattering to determine their shape, size, and mass per unit length. All of the micelles are hollow cylinders of well-defined size. The P740 and P750 cylinders are essentially monolayers of macrocycles crosslinked by water, probably in an arrangement similar to that of crystals of chlorophyll derivatives. The P865 micelle is m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(53 citation statements)
references
References 25 publications
6
47
0
Order By: Relevance
“…The possibility of an antiparallel dimer building block for the aggregate structure is thus rejected. It was inferred from small-angle neutron scattering that hydrated Chl a forms monolayers in a nonpolar solvent that organize into tubular micelles with a fixed radius of ∼57Å, with the phytyl chains on the outside, and with solvent molecules in the interior (6,20 ). Such a tube filled with solvent is very difficult to reconcile with the NMR data, since a response of the n-heptane was not yet observed in any of the datasets.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility of an antiparallel dimer building block for the aggregate structure is thus rejected. It was inferred from small-angle neutron scattering that hydrated Chl a forms monolayers in a nonpolar solvent that organize into tubular micelles with a fixed radius of ∼57Å, with the phytyl chains on the outside, and with solvent molecules in the interior (6,20 ). Such a tube filled with solvent is very difficult to reconcile with the NMR data, since a response of the n-heptane was not yet observed in any of the datasets.…”
Section: Discussionmentioning
confidence: 99%
“…When exposed to H 2 O it forms an aggregate. Such aggregates represent a paradigm for chlorophyll stacking in the chlorosome light-harvesting antennae found in some green photosynthetic bacteria (12,13). Thus, chlorophyll aggregates can form proteinfree light-harvesting antennae, which is of potential interest for artificial photosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Upfi eld aggregation shifts up to ~5 ppm are observed, mostly induced by ring currents. The shift pattern is in agreement with models for the Chl a/water aggregates that assume strong overlap between the rings A and the rings C and E of adjacent molecules forming stacks (Worcester et al, 1986). In addition, in a 2D 13 C-13 C RFDR spectrum recorded with a long mixing time of τ m = 10 ms, several cross-peaks are observed that can be attributed to intermolecular transfer (Fig.…”
Section: Aggregated Hydrated Chlorophyll (Chl A/ H 2 O) As a Modesupporting
confidence: 75%
“…The crucial evidence is that the in vitro aggregation of BChl c leads to similar structures and spectroscopic properties as occur in the natural system (for review, see Tamiaki et al, 2002). Small-angle neutron scattering studies have indicated cylindrical shaped micelles for aggregates prepared in organic media (Worcester et al, 1986). In addition, various spectroscopic methods suggest a highly ordered structure of both aggregated BChl c and the chlorosomes (Griebenow et al, 1991;Matsuura et al, 1993;Hildebrandt et al, 1994).…”
Section: Introductionmentioning
confidence: 98%